Pertumbuhan Tanaman Kacang Tanah (Arachis hypogea L. Merril) Setelah Aplikasi Azotobacter chroococcum Dan Pupuk NPK - Dewikusuma Ikhsani; Reginawanti Hindersah; Diyan Herdiyantoro (Faculty of Agriculture, Pattimura University, 2018)
The combination of biological fertilizers and chemical fertilizers can support the concept of sustainable integrated farming and minimize the adverse impacts of chemical fertilizers. Azotobacter sp. is a soil microbe that used as a biological fertilizer because it can fix N and produce phytohormones which are crucial for plant growth. This research aims to study the growth of peanut plants after Azotobacter chroococcum and NPK fertilizer application. This research was conducted on July-November 2016 in field trials of PT. Pupuk Kujang, Cikampek, West Java with a height of 25 m above sea level. The experiments were performed using a randomized block design with three treatments, 2 L / ha Azotobacter chroococcum, 300 kg / ha of NPK and 2 L / ha Azotobacter chroococcum + 150 kg / ha of NPK with four replications. The results showed treatment with a dose of 2 L / ha Azotobacter chroococcum + 150 kg / ha of NPK fertilizer can increase the growth of plant height and root dry weight, whereas treatment with a dose of 300 kg / ha of NPK most improve plant shoot dry weight. Keywords: Azotobacter chroococcum, NPK, Plant Growth.